PERILAKU IBU RUMAH TANGGA DALAM MENGGUNAKAN KELAMBU DI WILAYAH KERJA PUSKESMAS KABUKARUDI KABUPATEN SUMBA BARAT - ANDERIAS TARAWATU ORA (Poltekkes Kemenkes Kupang, 2016)
Introduction: malaria is a contagious disease that is still a public health problem in the world. To combat malaria incidence in western Sumba district, west of Sumba district health department has done kelambunisasi program. However, kelambunisasi program less effective in reducing the incidence of malaria in the region of kabukarudi health centers. Method: this type of research is explanatory research with cross sectional design. sample in this study amounted to 137 housewifes. Collecting data using questionnaires. Data was analyzed by univariate, bivariate and multivariate analyzes. Results & Conclusion: of the bivariate analysis, there are four variables related include perceptions (p value 0.000), attitude (p value 0.020), perception of support for families (p value 0.000) and keterpapaplran information (p value 0.015). The result: a multivariate analysis to get the most dominant factor is the perception of the support of the head of the family (OR 0288), and exposure information (OR 3.569), perception (OR 2.452), occupation (OR 0288).